Pendampingan Kerajinan Kolase untuk Meningkatkan Kemampuan Motorik Halus dan Kreativitas anak Migran di PKBM PNF KBRI Kuala Lumpur - Wardatusofiyah; Mahsun, Moch; Suwari (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
This community service activity aims to improve the fine motor skills and creativity of lower-grade migrant children through collage craft mentoring at the Community Learning Center (PKBM PNF) at the Indonesian Embassy in Kuala Lumpur. The program was implemented over 26 days using a participatory, service-learning-based method, encompassing planning, outreach, practice, and evaluation. Children were trained in cutting, pasting, patterning, and adapting materials to suit their own ideas. Observations showed significant improvements in hand-eye synchronization, accuracy, patience, focus, and the ability to demonstrate creativity through collage work. Furthermore, this activity fostered social values ​​such as discipline, responsibility, cooperation, and independence. Therefore, collage craft mentoring is an educational, fun, and effective learning method in supporting the development of fine motor skills and creativity in lower-grade migrant children.